Variation Aware Analog and Mixed-Signal Circuit Design in Emerging Multi-Gate CMOS Technologies - Fulde, Michael; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Since scaling of CMOS is reaching the nanometer area serious limitations enforce the introduction of novel materials, device architectures and device concepts. Multi-gate devices employing high-k gate dielectrics are considered as promising solution overcoming these scaling limitations of conventional planar bulk CMOS. Variation Aware Analog and Mixed-Signal Circuit Design in Emerging Multi-Gate CMOS Technologies provides a technology oriented assessment of analog and mixed-signal circuits in emerging high-k and multi-gate CMOS technologies. Closing the gap from technology to design a detailed insight into circuit performance trade-offs related to multi-gate and high-k device specifics is provided. The new effect of transient threshold voltage variations is described with an equivalent model that allows a systematic assessment of the consequences on circuit level and the development of countermeasures to compensate for performance degradation in comparators and A/D converters. Key analog, mixed-signal and RF building blocks are realized in high-k multi-gate technology and benchmarked against planar bulk. Performance and area benefits, enabled by advantageous multi-gate device properties are analytically and experimentally quantified for reference circuits, operational amplifiers and D/A converters. This is based on first time silicon investigations of complex mixed-signal building blocks as D/A converter and PLL with multi-gate devices. As another first, the integration of tunnel transistors in a multi-gate process is described, enabling devices with promising scaling and analog properties. Based on these devices a novel reference circuit is proposed which features low power consumption.
Analog Properties of Multi-Gate MOSFETs -- High-k Related Design Issues -- Multi-Gate Related Design Aspects -- Multi-Gate Tunneling FETs -- Conclusions and Outlook.
Keywords: Engineering; Systems engineering; Optical materials; Engineering; Circuits and Systems; Optical and Electronic Materials